The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11064-011-0581-4
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CLEC16A in Activation of Astrocytes After LPS Treated

Abstract: CLEC16A, C-type lectin domain family 16, member A was recently found to be associated with inflation process in the autoimmune diseases. In this study, we elucidated the dynamic expression changes and localization of CLEC16A in lipopolysaccharide (LPS)-induced neuroinflammatory processes in adult rats. CLEC16A expression was strongly induced in active astrocytes in inflamed cerebral cortex. In vitro studies indicated that the up-regulation of CLEC16A may be involved in the subsequent astrocyte activation follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 31 publications
(23 reference statements)
1
12
0
Order By: Relevance
“…CLEC16A expression was strongly induced in active astrocytes in inflamed cerebral cortex. In vitro studies indicated that the up-regulation of CLEC16A may be involved in astrocyte activation following LPS challenge [72]. …”
Section: Genetic Component In Type 1 Diabetesmentioning
confidence: 99%
“…CLEC16A expression was strongly induced in active astrocytes in inflamed cerebral cortex. In vitro studies indicated that the up-regulation of CLEC16A may be involved in astrocyte activation following LPS challenge [72]. …”
Section: Genetic Component In Type 1 Diabetesmentioning
confidence: 99%
“…CLEC16A, however, could have evolved to play a much different role in humans (as seen by its preferential expression in immune cells). Another study found that CLEC16A was induced in activated rat astrocytes harvested from the inflamed cerebral cortices of rats that have been injected with lipopolysaccharide (LPS), and suggests that it may be involved in the astrocyte-mediated immune response [26]. This result merely correlates the presence of CLEC16A with astrocyte inflammation, and needs to be investigated in further detail.…”
Section: Introductionmentioning
confidence: 99%
“…After pulp injury regulation of innervation and inflammation is important to preserve pulpal health trough both regulation of re-innervation and intrapulpal tissue pressure. Significant markers for neural development up-regulated in pulp cells after EMD treatment were CLEC16A [33] with effect on activation and control of neuroinflammation, CNTNAP5 involved in CNS development [34] and NFASC that regulate neural development and axon innervations [35]. …”
Section: Discussionmentioning
confidence: 99%